Damage to left frontal regulatory circuits produces greater positive emotional reactivity in frontotemporal dementia. (March 2015) - Sturm, Virginia E.; Yokoyama, Jennifer S.; Eckart, Janet A.; Zakrzewski, Jessica; Rosen, Howard J.; Miller, Bruce L.; Seeley, William W.; Levenson, Robert W.
Abstract: Positive emotions foster social relationships and motivate thought and action. Dysregulation of positive emotion may give rise to debilitating clinical symptomatology such as mania, risk-taking, and disinhibition. Neuroanatomically, there is extensive evidence that the left hemisphere of the brain, and the left frontal lobe in particular, plays an important role in positive emotion generation. Although prior studies have found that left frontal injury decreases positive emotion, it is not clear whether selective damage to left frontal emotion regulatory systems can actually increase positive emotion. We measured happiness reactivity in 96 patients with frontotemporal dementia (FTD), a neurodegenerative disease that targets emotion-relevant neural systems and causes alterations in positive emotion (i.e., euphoria and jocularity), and in 34 healthy controls. Participants watched a film clip designed to elicit happiness and a comparison film clip designed to elicit sadness while their facial behavior, physiological reactivity, and self-reported emotional experience were monitored. Whole-brain voxel-based morphometry (VBM) analyses revealed that atrophy in predominantly left hemisphere fronto-striatal emotion regulation systems including left ventrolateral prefrontal cortex, orbitofrontal cortex, anterior insula, and striatum was associated with greater happiness facial behavior during the film ( p FWE < .05). Atrophy in left anterior insula and bilateral frontopolar cortex was also associated with higher cardiovascular reactivity (i.e., heart rate and blood pressure) but not self-reported positive emotional experience during the happy film ( p  < .005, uncorrected). No regions emerged as being associated with greater sadness reactivity, which suggests that left-lateralized fronto-striatal atrophy is selectively associated with happiness dysregulation. Whereas previous models have proposed that left frontal injury decreases positive emotional responding, we argue that selective disruption of left hemisphere emotion regulating systems can impair the ability to suppress positive emotions such as happiness.